2020
DOI: 10.1039/d0ra08358e
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of chitosan membranes for visible-light-driven photocatalytic degradation of tetracycline hydrochloride

Abstract: Chitosan membrane exhibited a good visible light photocatalytic activity over tetracycline hydrochloride degradation. The corresponding degradation mechanism was investigated as shown above.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 37 publications
3
5
0
Order By: Relevance
“…Thus, the indirect band gaps energy of ZnO, Chitosan, ZnO/Chitosan and MWCNTs/ZnO/Chitosan were determined to be 2.75, 2.47, 0.97 and 0.8 eV, respectively. The calculated bandgap values of Chitosan and ZnO nanoparticles were comparable with previous studies 47 , 48 , respectively. The results obviously showed that after adding Chitosan to ZnO, the bandgap value reduces gradually and subsequently results to prepare condition for the photocatalytic removal of MB dye under the UV light irradiation.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Thus, the indirect band gaps energy of ZnO, Chitosan, ZnO/Chitosan and MWCNTs/ZnO/Chitosan were determined to be 2.75, 2.47, 0.97 and 0.8 eV, respectively. The calculated bandgap values of Chitosan and ZnO nanoparticles were comparable with previous studies 47 , 48 , respectively. The results obviously showed that after adding Chitosan to ZnO, the bandgap value reduces gradually and subsequently results to prepare condition for the photocatalytic removal of MB dye under the UV light irradiation.…”
Section: Resultssupporting
confidence: 89%
“…The E VB and E CB of ZnO were measured to be 2.615 eV and − 0.135 eV, respectively. According to Liang et al, 47 , the LUMO energy level potential (E LUMO ) of the Chitosan was calculated to be − 0.35 eV. In addition, based on the bandgap of 2.47 eV for the Chitosan that was given before, the E HOMO of the Chitosan was determined 2.1 eV.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the indirect band gaps energy of ZnO, Chitosan, ZnO/Chitosan and MWCNTs/ZnO/Chitosan were determined to be 2.75, 2.47,0.97 and 0.8 eV, respectively. The calculated bandgap values of Chitosan and ZnO nanoparticles were comparable with previous studies 35,36 , respectively. The results obviously showed that after adding Chitosan to ZnO, the bandgap value reduces gradually and subsequently results to prepare condition for the photocatalytic removal of MB dye under the UV light irradiation.…”
Section: Optical and Electronic Characteristics Of The Zno Zno/chitosan And Mwcnts/zno/chitosan Nanocompositessupporting
confidence: 90%
“…The UV-Visible spectra and energy bandgap (E g ) of synthesized samples are illustrated in Fig. 7a ZnO nanoparticles were comparable with previous studies 35,36 , respectively. The results obviously showed that after adding Chitosan to ZnO, the bandgap value reduces gradually and subsequently results to prepare condition for the photocatalytic removal of MB dye under the UV light irradiation.…”
Section: Optical and Electronic Characteristics Of The Zno Zno/chitosan And Mwcnts/zno/chitosan Nanocompositessupporting
confidence: 88%
See 1 more Smart Citation